Biological impacts of hypomagnetic fields in space environment: implications for artificial magnetic field provision in long-duration spaceflight - Dang, Nhat; Keller, Jason; Barnes, Frank (Frontiers in Space Technologies, 2025)
Life on Earth evolved and exists within the geomagnetic field which currently ranges from approximately 25–65 µT. Voyages beyond Earth’s magnetosphere expose astronauts to the unique conditions of deep space, characterized by significantly reduced magnetic fields ranging from 2 to 8 nT. This review examines the growing body of evidence concerning the biological impacts of hypomagnetic and altered magnetic fields on humans and other organisms, highlighting the implications for long-duration spaceflight and space mission. Research using human cell cultures and mammalian models indicates that exposure to varying magnetic field conditions, including hypomagnetic fields (HMF), can induce diverse biological effects. These include changes in cellular proliferation, nervous system function, oxidative stress reactive oxygen species levels, and DNA integrity, with outcomes often dependent on specific field intensity, frequency, and length of exposures. Furthermore, HMF exposure has been shown to affect bacterial behavior and the human microbiome, potentially altering antibiotic resistance and increasing risks of infection, given the compromised immune function astronauts may experience in space. Considering these biological impacts on the wellbeing of astronauts on long-term space mission, providing artificial magnetic fields onboard spacecraft is proposed as a critical strategy to mitigate HMF effects, support astronaut health, and enhance the feasibility and safety of future deep space missions.